COVID-19 and Male Infertility: Is There a Role for Antioxidants? - Thomas Kalfas; Aris Kaltsas; Evangelos N. Symeonidis; Asterios Symeonidis; Athanasios Zikopoulos; Efthalia Moustakli; Chara Tsiampali; Georgios Tsampoukas; Natalia Palapela; Athanasios Zachariou; Nikolaos Sofikitis; Fotios Dimitriadis (MDPI AG, 2023)
Coronavirus disease 19 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), jeopardizes male fertility because of the vulnerability of the male reproductive system, especially the testes. This study evaluates the effects of the virus on testicular function and examines the potential role of antioxidants in mitigating the damage caused by oxidative stress (OS). A comprehensive PubMed search examined exocrine and endocrine testicular function alteration, the interplay between OS and COVID-19-induced defects, and the potential benefit of antioxidants. Although the virus is rarely directly detectable in sperm and testicular tissue, semen quality and hormonal balance are affected in patients, with some changes persisting throughout a spermatogenesis cycle. Testicular pathology in deceased patients shows defects in spermatogenesis, vascular changes, and inflammation. Acute primary hypogonadism is observed mainly in severely infected cases. Elevated OS and sperm DNA fragmentation markers suggest redox imbalance as a possible mechanism behind the fertility changes. COVID-19 vaccines appear to be safe for male fertility, but the efficacy of antioxidants to improve sperm quality after infection remains unproven due to limited research. Given the limited and inconclusive evidence, careful evaluation of men recovering from COVID-19 seeking fertility improvement is strongly recommended.